Komposisi Nutrisi Rumput Laut Coklat (Phaeophyta) dan Merah (Rhodophyta) Asal Perairan Teluk Sepang Kota Bengkulu - Utami, Maya Angraini Fajar; Wilopo, Mukti Dono; Permatasari, Nurul; herliany, vivien (Universitas Bengkulu, 2023)
Seaweeds have potential uses as functional foods. But until now, there is still few information about the nutritional composition of seaweeds, especially from Teluk Sepang Beach, Bengkulu City. This study was held to examine the chemical characteristics of brown and red seaweeds from Teluk Sepang Beach, Bengkulu City. This research was carried out in November 2021-March 2022. This research used descriptive exploratory method by analyzing the proximate composition of 8 species of seaweeds (4 species of brown seaweeds and 4 species of red seaweeds). Water, protein, crude fat, ash and crude fiber content refer to the AOAC (2016) procedure while carbohydrate content is calculated based on by difference. The chemical characteristics of seaweeds (water content, ash, crude protein, crude fiber, crude fat and carbohydrates content) varied from one species to another. But in general the proximate composition of all seaweeds species was still in the range of values ​​found in seaweeds. The largest composition in seaweesd is carbohydrates (13.644% - 69.91±0.71%) and ash, which have an important role for humans nutrition and the food industry. The content of protein (0.97±0.33%. - 2.88±0.23%) and crude fat (0.19±00% - 4.12±0.32%) in seaweeds is relatively low so it can be used as low fat foods. Crude fiber in seaweeds(1.16±0.16% - 7.65±0.53%) showed that seaweeds can be used as functional foods.